Boundaries of Care: Community Health Workers in the United States - Logan, Ryan I. (Lexington Books, 2022)
In Boundaries of Care, Ryan I. Logan details the lived experience of community health workers (CHWs) – a present yet often invisible facet of the healthcare workforce. These workers participate in nonclinical services to enhance the health and well-being of their communities outside the walls of the clinic and social service agencies. Logan examines the boundaries of and barriers to care present in the experiences of CHWs, their relationships with clients, issues of professionalization, impacts of burnout and self-care, and the critical impacts of CHW advocacy. Told through first-hand accounts and interwoven with theory, Logan presents the key challenges facing this workforce and their potential to foster even greater well-being within their communities. The findings and recommendations from participants found within Boundaries of Care can inform and shape CHW programs both in the United States and abroad.